The effect of fiber diet on colonic cancer formation: the role of butyrate (Medical Journal of Indonesia, 2003)
The majority of colon cancers occur sporadically. They are thougth to be caused by non-inherited factors such as a combination of diet and environmental factors, which result in somatic mutations of specific genes. Among dietary factors butyrate which is derived from fermentable fibers may have important role as chemoprotector against colorectal cancer. The source of butyrate in daily diet mostly come from wheat products especially wheat bran. At molecular level, butyrate causes hystone acetylation, favours differentiation, induces apoptosis and regulates the expressions of various oncogens. These effects suggest that butyrate may be protective against colorectal cancers. (Med J Indones 2003; 12: 127-31)Keywords: colon cancer, dietary fiber, apoptosis